PROTAC-based therapeutics for targeting HPV oncoproteins in head and neck cancers - Nobendu Mukerjee; Dattatreya Mukherjee (Nano TransMed)
The increasing incidence of Human Papillomavirus (HPV)-related head and neck cancers, particularly oropharyngeal squamous cell carcinomas, highlights the need for advanced therapeutic options beyond the traditional modalities of surgery, radiation, and chemotherapy, which often lead to significant morbidity and lack specificity in targeting the molecular pathogenesis of the disease. Proteolysis Targeting Chimeras (PROTACs) present a novel therapeutic strategy, leveraging the ubiquitin-proteasome system to specifically degrade the oncogenic HPV proteins E6 and E7. This targeted approach not only potentially reduces the side effects associated with conventional treatments but also directly interrupts the cancer-promoting activities of these proteins, offering a promising avenue for more effective and less invasive treatment of HPV-associated malignancies.